The Influence of Mass Media on Public Perception of Criminal Cases: A Qualitative Approach - Fadhilah, Nurul (Journal of Linguistica, 2025)
This study explores the influence of mass media on public perception of criminal cases through a qualitative lens. Mass media, including television, newspapers, and digital platforms, plays a significant role in shaping public opinion, often framing criminal events in ways that can influence societal judgments, emotional responses, and perceptions of guilt or innocence. Using in-depth interviews and content analysis, the research investigates how media narratives, sensationalism, and selective reporting contribute to the formation of public bias and moral panic. The findings reveal that repetitive exposure to crime-related content can distort reality and amplify fear, while media framing tends to reinforce stereotypes and influence the perceived severity of crimes. This study contributes to a deeper understanding of media effects on public consciousness and emphasizes the need for more balanced and ethical journalism in crime reporting.